Myocardial Perfusion, Function, and Dyssynchrony in Heart Failure Patients: Baseline Results from the SPECT Imaging Ancillary Study of the Heart Failure and A Controlled Trial Investigating Outcomes of Exercise TraiNing (HF-ACTION) Trial - Atchley, Allen E. (2009)
BACKGROUND: There are currently limited data on the relationships between resting perfusion abnormalities, LVEF, New York Heart Association (NYHA) functional class, and exercise capacity as defined by peak VO(2) and six-minute walk test in patients with heart failure and reduced left ventricular ejection fraction. Furthermore, the association between resting perfusion abnormalities and left ventricular dyssynchrony is currently unknown. This manuscript addresses The Heart Failure and A Controlled Trial Investigating Outcomes of Exercise TraiNing (HF-ACTION) gated SPECT imaging (gSPECT) substudy baseline results. METHODS: HF-ACTION was a multi-center, randomized controlled trial of aerobic exercise training vs. usual care in 2331 stable patients with LVEF ≤35% and NYHA class II–IV heart failure symptoms treated with optimal medical therapy. Subjects enrolled in the HF-ACTION sub-study underwent resting Tc 99m tetrofosmin gSPECT at baseline (n=240). Images were evaluated for extent and severity of perfusion abnormalities using a 17-segment and a 5-degree gradation severity score (SRS). LV function and dyssynchrony were assessed using validated available commercial software. RESULTS: The average age of patients enrolled was 59, 69% were male, 63% were white, and 33% were African-American. Of the 240 participants, 129 (54%) were ischemic and 111 (46%) were non-ischemic in etiology. The median LVEF by gated SPECT for the entire cohort was 26%. Among the nuclear variables, there was a modest correlation between LVEF and SRS (r= − 0.31, p < 0.0001) and there were stronger correlations between phase SD and SRS (r= 0.66, p< 0.0001) as well as phase SD and LVEF (r= −0.50, p< 0.0001). Patients with NYHA class III symptoms had more severe and significant degrees of dyssynchrony, median phase SD 54°, than those with NYHA class II symptoms, median phase SD 39° (p value=0.001). Patients with an ischemic etiology had a higher SRS (p< 0.0001) and significantly more dyssynchrony (p< 0.0001) than those who were nonischemic. However, there was no difference in LVEF or objective measures of exercise capacity between these groups. With respect to peak VO2, there was a weak correlation with LVEF (r = 0.18, p= 0.006) and no correlation with SRS (r = −0.04, p= 0.59) or with dyssynchrony (r= −0.13, p= 0.09). A weak, but statistically significant correlation between SRS and 6-minute walk was observed (r= −0.15, p = 0.047). CONCLUSIONS: Gated SPECT imaging can provide important information in patients with heart failure due to severe LV dysfunction including quantitative measures of global systolic function, perfusion and dyssynchrony. These measurements are modestly but significantly related to symptom severity and objective measures of exercise capacity.